(untitled) (Journal of Plant Disease Sciences, 2019)
Coriander (Coriandrum sativum L.), a native of Mediterrian region is now commercially grown as spice crop in India. India is the biggest producer, consumer and exporter of coriander in the world with producing 482 thousands metric tonnes from the 5305 thousand hectares and productivity of 0.9 metric tonnes per hectare in 2011-12 (Anonymous, 2012). Major coriander growing states are Andhra Pradesh, Karnataka, Rajasthan, Gujarat, Madhya Pradesh, Uttar Pradesh, Bihar and Rajasthan. The aromatic odour and taste of coriander fruits are its essential oil containing 0.03 to 2.6 percent (Nadeem et al., 2013). Coriander seeds are used as culinary herb. Although, the area and production of coriander is increasing year after year but the productivity is stagnant in spite of development of high yielding varieties and improved package of production technology. One of the major reasons behind this fact is the incidence of many diseases. Powdery mildew disease caused by Erysiphe polygoni is an important disease in coriander growing area of Madhya Pradesh and adjoining districts of Rajasthan and Uttar Pradesh. The disease is air borne and survives in the form of chlamydospore. The disease symptoms appear in the form of white circular patches on young parts of stems, branches, leaves, petioles and fruits, which causes severe yield losses and also deteriorate the quality of seeds. Powdery mildew disease reduces the plant growth and increased the flower drop which reduced seed formation. Affected field showed 20 -30 percent less seed production. Breeding effort to high yielding varieties with resistant to powdery mildew disease in coriander are very limited, therefore control of powdery mildew is difficult because of its air borne nature and rapid disease development with intensive cultivation of the susceptible host crop and recurrence of the disease in the same field led to explore the possibility of new generation fungicides against powdery mildew.